2019
DOI: 10.1155/2019/1468502
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Isolated fromCalea unifloraLess. Promote Anti-Inflammatory and Antioxidant Effects in Mice Neutrophils (Ex Vivo) and in Mice Pleurisy Model (In Vivo)

Abstract: The literature shows that phenolic compounds possess important antioxidant and anti-inflammatory activities; however, the mechanism underlying these effects is not elucidated yet. The genus Calea is used in folk medicine to treat rheumatism, respiratory diseases, and digestive problems. In this context, some phenolic compounds were isolated with high purity from Calea uniflora Less. and identified as noreugenin (NRG) and α-hydroxy-butein (AH-BU). The aim of this study was to analyze the effect of these compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Notably, we also found that among these differential compounds a phenolic acid compound, noreugein, was only present in D. officinale at low altitude, while two lipid compounds, Lyso PE20 : 4 and its isomer, were only present in D. officinale at high altitude, as shown in Figure 6. Noreugein is a phenolic acid compound known to have anti‐inflammatory and antioxidant activity and may exhibit potent anti‐inflammatory activity by inhibiting inflammatory cells (increasing neutrophil apoptosis) [40,41] . Lyso PE 20 : 4 and its isomers are poorly studied, but some studies have reported that it is a metabolite relevant to the pathogenesis of collagen‐induced arthritis [42] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we also found that among these differential compounds a phenolic acid compound, noreugein, was only present in D. officinale at low altitude, while two lipid compounds, Lyso PE20 : 4 and its isomer, were only present in D. officinale at high altitude, as shown in Figure 6. Noreugein is a phenolic acid compound known to have anti‐inflammatory and antioxidant activity and may exhibit potent anti‐inflammatory activity by inhibiting inflammatory cells (increasing neutrophil apoptosis) [40,41] . Lyso PE 20 : 4 and its isomers are poorly studied, but some studies have reported that it is a metabolite relevant to the pathogenesis of collagen‐induced arthritis [42] .…”
Section: Resultsmentioning
confidence: 99%
“…Noreugein is a phenolic acid compound known to have anti-inflammatory and antioxidant activity and may exhibit potent antiinflammatory activity by inhibiting inflammatory cells (increasing neutrophil apoptosis). [40,41] Lyso PE 20 : 4 and its isomers are poorly studied, but some studies have reported that it is a metabolite relevant to the pathogenesis of collagen-induced arthritis. [42] However, further studies are needed.…”
Section: Screening the Differential Metabolites Of D Officinale At Di...mentioning
confidence: 99%
“…The most interesting thing is that the content of eugenitol and methyl sulfate in serum metabolites of pet cats fed with compound Bacillus increased significantly compared with the control group, but no similar pattern was found in fecal metabolomics. Eugenitol has a similar structure with biflorin and noreugeninshare, which have common structures such as methylchromone with two hydroxyl groups, and they had been reported to exert anti-inflammatory effects [ 49 , 50 ]. In addition, studies have further shown that eugenitol had the effects of anti-inflammatory and antioxidants through LPS-induced BV2 cell activation experiments [ 51 ].…”
Section: Discussionmentioning
confidence: 99%